2018
DOI: 10.1080/10400435.2018.1464080
|View full text |Cite
|
Sign up to set email alerts
|

Assessing manual wheelchair caster design for mobility in winter conditions

Abstract: Wheelchair users who live in cold climates are faced with daily difficulties related to personal independence and societal inclusion as their assistive devices are unable to overcome the physical barriers created by snow and ice. The purpose of the research was to evaluate four commercially available casters to determine which caster performed best on snow-covered surfaces. Performance measures included: travel time, force transfer through the palms of the hands, number of propulsive movements, static resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although products and technologies were the focus of almost half of the located papers, not all studies evaluated product performance and the wide diversity in products tested, methods used, and product user populations makes definitive conclusions on performance effectiveness impossible. Products with at least some minimal performance evaluation included wheelchair casters, 16 power wheelchairs, 17 , 18 mobility scooters, 35 , 39 cane or crutches, 19 , 20 , 40 and shoes or cleats. 21 , 22 , 34 , 36 Although there are some winter-specific products available on vendor websites, most of them do not have any supporting research evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although products and technologies were the focus of almost half of the located papers, not all studies evaluated product performance and the wide diversity in products tested, methods used, and product user populations makes definitive conclusions on performance effectiveness impossible. Products with at least some minimal performance evaluation included wheelchair casters, 16 power wheelchairs, 17 , 18 mobility scooters, 35 , 39 cane or crutches, 19 , 20 , 40 and shoes or cleats. 21 , 22 , 34 , 36 Although there are some winter-specific products available on vendor websites, most of them do not have any supporting research evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who use manual wheelchairs (MWC) as their primary means of mobility typically experience seasonal-related accessibility barriers in the winter months ( 1 ). Environmental barriers such as icy or snow-covered surfaces and snow windrows have been reported as frequent barriers to mobility in studies of MWC users in Manitoba ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…These seasonal barriers can influence both the frequency and quality of community participation. Findings from a 12-month longitudinal study of 11 wheelchair users confirmed they made fewer trips per day and wheeled shorter distances at slower speeds during non-summer (vs. summer) months, on winter days with (vs. without) snow accumulation, and on winter days when temperatures were below (vs. above) 0 ° C ( 1 ). A focus group with eight Manitobans who use wheelchairs concluded that winter community participation should be considered a right for all citizens ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings from the study of Lin and Sprigle [ 3 ] who found a decrease in the propulsion efforts with the increased percentage weight on the rear wheels. In addition, the effect of caster design on wheelchair mobility in winter conditions has been reported [ 15 ]. Based on the findings reported in the abovementioned studies, there seems to be a direct correlation between wheel/caster configuration and rolling resistance that, ultimately, influences the physiological demand for manual wheelchair propulsion.…”
Section: Introductionmentioning
confidence: 99%